Kajian Literatur tentang Teknik Pengujian Tegangan Tinggi Impuls pada Sistem Distribusi Listrik : Literature Review on High-Voltage Impulse Testing Techniques in Electrical Distribution Systems - Suhesya, Adelia Putri (Institut Riset dan Publikasi Indonesia, 2024)
This literature review presents a comprehensive overview of impulse high voltage testing techniques applied in electrical distribution systems. Impulse high-voltage testing is required to evaluate the insulation resistance of electrical equipment to sudden voltage surges, such as those induced by lightning or switching disturbances. Through collecting data from scientific sources such as journals and electronic databases, this review classifies various testing techniques, including tests with lightning impulses and switching impulses, and discusses recent technological developments such as the use of advanced sensors and online monitoring systems. It also discusses comparisons between testing techniques, identifying the advantages, disadvantages, and challenges faced in the application of these techniques. It is hoped that this literature review will provide practical guidance and valuable academic contributions to electrical engineering professionals, as well as encourage further research into improving the reliability and safety of electrical distribution systems through impulse high voltage testing.